Accepting Bilingualism in English-speaking Canada, Testing the Limits of the Official Languages Policy in the Federal Public Service, 1962-1972 - Moyer, Norman (Université d'Ottawa / University of Ottawa, 2014)
This work is concerned with the way that official bilingualism emerged as a part of English-Canadian values in the 1960s. Much of this work is about the effort in the 1960s to change the federal public service from a stronghold of English-speaking Canada to an organisation where English-speaking and French-speaking Canadians could work in their own language on an equal footing. The archival records of the Professional Institute of the Public Service provide detailed insight into this change and the resistance to it. It is the thesis of this work that the adaptation to official bilingualism in the Public Service of Canada played a key role in setting English-speaking attitudes to bilingualism. The struggle to define and impose official bilingualism in the federal public service was a testing ground for the evolution of bilingualism in English-speaking Canada as a whole. As much of English-speaking Canada accepted the value of bilingualism in principle, the public service worked out the practical ramifications of this culture change. The result was a slow and only partial progress toward effective bilingualism in the federal public service and in Canada as a whole.
Keywords: Bilingualism; English-speaking Canada